The host rock of the Central Patagonian Batholith in Gastre: further insights on the Late Triassic to Early Jurassic deformation in the region - Zaffarana, Claudia Beatriz (2012)
Fil: Zaffarana, Claudia Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET). Departamento de Ciencias Geológicas, Facultad de Ciencias Exactas y Naturales, Universidad de Buenos Aires. Argentina.